Environmentally driven forecasts of northern rock sole (Lepidopsetta polyxystra) recruitment in the eastern Bering Sea. (20th November 2019) - Cooper, Daniel; Rogers, Lauren A.; Wilderbuer, Thomas
Abstract: Northern rock sole recruitment in the eastern Bering Sea has been hypothesized to (a) depend on wind‐driven surface currents linking spawning and nursery areas, (b) be density‐dependent, and (c) be negatively impacted by cold bottom temperatures over a large nursery area during the first summer of life. A suite of models was developed to test these hypotheses. Data included 32 years of recruitment and spawning biomass estimates derived from a stock assessment model and wind and temperature indices customized to the environmental exposure of age‐0 northern rock sole in the eastern Bering Sea. The predictive ability of the models was evaluated, and the models were used to forecast recruitment to age‐4 for recent year classes which are poorly retained by the standard multi‐species bottom trawl survey gear. Models which included wind and temperature indices performed better than a naïve forecast based on the running mean. The best‐performing model was a categorical model with wind and temperature thresholds, which explained 49% of the variation in recruitment. Ricker models performed more poorly than models without a spawning biomass term, providing no evidence that recruitment is related to stock size. The models forecast higher recruitment for the most recent year classes (2015–2018) than for prior year classes with observed poor recruitment (2006–2013). These environment‐based recruitment forecasts may improve recruitment estimates for the most recent year classes and facilitate study of the effects of future climate change on northern rock sole population dynamics.